The missionary work of the first Anglican Bishop of Natal, the Rt. Reverend John William Colenso, between the years 1852-1873 - Burnett, B B (Rhodes University, Faculty of Humanities, Department of History, 1947)
At the outset it had been my intention to make only the slightest of references to the Church Controversy in which Bishop Colenso was involved and to have touched only lightly on his theological position. Apart from anything else I hesitated to enter the arena in which so many had already collided violently and where my own prejudices might be enlisted on one side or the other. It became evident however that Colenso the Controversialist, the Theologian could not be dissociated from Colenso the missionary, without giving an inadequate, and even misleading history of his missionary activities. The Controversy had a serious and deleterious effect on his missionary work, and no estimate of the value of a missionary's labours would be valid without some consideration of his teaching, more especially when his orthodoxy is suspect. I have therefore dealt as briefly as I could with these questions in Chapter V because of their relevance, and because to produce a work on an ecclesiastic without some reference to his tenets would be like writing a biography of Louis Botha without any allusion to his political 'faith', or of Wellington, without any mention of Waterloo. it would represent a distortion of history to write about a Missionary Bishop as though he were an amateur politician, or of a missionary as though he were interested only in finance and administration.
Keywords: Colenso, John William, 1814-1883